2014
DOI: 10.1186/1471-2393-14-108
|View full text |Cite
|
Sign up to set email alerts
|

Availability of drugs and medical supplies for emergency obstetric care: experience of health facility managers in a rural District of Tanzania

Abstract: BackgroundProvision of quality emergency obstetric care relies upon the presence of skilled health attendants working in an environment where drugs and medical supplies are available when needed and in adequate quantity and of assured quality. This study aimed to describe the experience of rural health facility managers in ensuring the timely availability of drugs and medical supplies for emergency obstetric care (EmOC).MethodsIn-depth interviews were conducted with a total of 17 health facility managers: 14 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
68
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 20 publications
(23 reference statements)
7
68
2
Order By: Relevance
“…Some needed drugs were either expiring or not available due to delayed reimbursement, untimely replenishment of stocks and providers’ lack of funding for transport to collect drugs from the central medical store. These findings, which are consistent with evidence from several studies, partly explains health workers’ poor adherence to the free care policy and increased involvement in parallel drug supply systems [12,17,2631]. …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Some needed drugs were either expiring or not available due to delayed reimbursement, untimely replenishment of stocks and providers’ lack of funding for transport to collect drugs from the central medical store. These findings, which are consistent with evidence from several studies, partly explains health workers’ poor adherence to the free care policy and increased involvement in parallel drug supply systems [12,17,2631]. …”
Section: Discussionsupporting
confidence: 90%
“…Use of service charters to curb informal payments to service providers [9], active health facility committees (HFCs) including financial management [1012], timely payment of providers [13], regular and uninterrupted drug supply [13], availability of clear guidelines on use of user fee replacement grants [14], an effective staff sanction framework, which reduces health worker absenteeism [15], have enabled health facilities to effectively implement free healthcare policies. In contrast, barriers to health facilities implementing free healthcare policies include weak decentralization [10,1618]; poor supervision and monitoring [19,20]; weak referral systems [17]; absence of written implementation guidelines [14,21]; shortage of staff and inconsistent recording and reporting [10,20]; low social accountability and community involvement [9,22–24]; delayed payment of providers [12,21,25]; lack of adequate drug stock [17,18,24,2631]; mistrust between providers and patients [19,3234]; absenteeism [10,15,20]; poorly motivated health workers [18,24]; lack of financial incentives [35]; preference for urban postings [19,36]; funding inadequacy in health facilities [16]; inadequate physical infrastructure [18,24,36]; unavailability of guidelines for use of user fee replacement fund [37] and unclear procedures for targeting beneficiaries [3]. …”
Section: Introductionmentioning
confidence: 99%
“…In line with previous studies, this investigation finds that the availability of essential obstetric drugs is strongly associated with a higher volume of delivery and postnatal care services at the HSCs (Mkoka et al, 2014). However, regrettably, about 42% of sub-centers are still devoid of all the essential obstetric drugs recommended by the Indian Public Health Standards.…”
Section: Discussionsupporting
confidence: 89%
“…A recent study has concluded that increased facility deliveries in India do not contribute to a reduction in maternal deaths because these facilities often have a weak drug and medical supply system, which leads to poor obstetric care quality (Randive, 2016). The lack of drugs has also been found to cause distrust between users and health care providers; it creates a difficult working environment and decreases health workers’ morale as well (Mkoka et al, 2014). All of these factors, when combined, could result in the low utilization of health care services.…”
Section: Discussionmentioning
confidence: 99%
“…inadequate supplies of commodities and drugs such as iron and folic acid [45], syphilis test kits, and HIV test kits, despite some of the drugs being cheap and the significant attention that has been given to HIV-related care in recent years in Uganda [45–48]. These findings are similar to findings in Tanzania [49], where restricted availability of medicines and medical supplies led to poor-quality obstetric care. Here solutions lie on the ‘supply side’, requiring further investigation in the local context as to whether the issue is at facility level (e.g.…”
Section: Discussionmentioning
confidence: 83%